2018
DOI: 10.1038/s41598-018-34998-0
|View full text |Cite
|
Sign up to set email alerts
|

Controlled electron injection facilitated by nanoparticles for laser wakefield acceleration

Abstract: We propose a novel injection scheme for laser-driven wakefield acceleration in which controllable localized electron injection is obtained by inserting nanoparticles into a plasma medium. The nanoparticles provide a very confined electric field that triggers localized electron injection where nonlinear plasma waves are excited but not sufficient for background electrons self-injection. We present a theoretical model to describe the conditions and properties of the electron injection in the presence of nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…What adds to the effect of enhanced and continuous injection is the presence of ion clusters. As was shown in [55] the potential of an ion nanoparticle injected into the wakefield eases the trapping condition. It can be argued that the same mechanism aids injection in our case (albeit to a smaller extent due to the smaller cluster size).…”
Section: Electron Trapping and Accelerationmentioning
confidence: 78%
See 1 more Smart Citation
“…What adds to the effect of enhanced and continuous injection is the presence of ion clusters. As was shown in [55] the potential of an ion nanoparticle injected into the wakefield eases the trapping condition. It can be argued that the same mechanism aids injection in our case (albeit to a smaller extent due to the smaller cluster size).…”
Section: Electron Trapping and Accelerationmentioning
confidence: 78%
“…This indicates that there are particles being trapped that have experienced equal positive and negative perpendicular impulse. In the setting of wakefields this is only possible if the electrons either traverse through the wakefield via a central path close to the laser propagation axis while gaining longitudinal momentum (i.e., through a slingshot mechanism in the vicinity of a cluster as discussed in [55]) or via a path that exhibits nonsymmetrical, fluctuating electric fields which have been observed in this study. The great variety of available perpendicular momenta at injection also gives an explanation for the high standard deviation in oscillation amplitude in Fig.…”
Section: Electron Trapping and Accelerationmentioning
confidence: 87%
“…At this condition, self-injection is not possible. Recently, electron injection mechanisms, such as ionization injection [39][40][41], density shock injection [42,43], and nanoparticle insertion [44,45], have been proposed and demonstrated. Because the laser should propagate 10 m for 100 GeV acceleration, the electron injection process should not degrade laser properties and should occur only at the beginning of the medium.…”
Section: Perspective Of Lwfa With Pw Lasersmentioning
confidence: 99%
“…A nanoparticle in plasma medium for LWFA can induce a highly localized injection, leading to an electron beam with a small emittance. A numerical study showed that a nanoparticle in plasma could facilitate a controllable injection to produce a high-quality 5-GeV electron beam with a 0.5-PW laser pulse [44]. Furthermore, a recent experimental study demonstrated nanoparticle-assisted laser wakefield acceleration with a nanoparticle-mixed helium gas jet [45].…”
Section: Perspective Of Lwfa With Pw Lasersmentioning
confidence: 99%
“…There have been theoretical studies on the use of a nanowire or nanoparticle for seeding electrons in LWFA. The use of a nanowire in the bubble regime was proposed by Shen et al 11 in 2007 and the use of a nanoparticle was investigated theoretically in 2018 by Cho et al 12 with multi-dimensional particle-in-cell (PIC) simulations. These new electron acceleration schemes use a nanowire or a nanoparticle to trigger the injection of electrons in the acceleration phase of the plasma wakes.…”
Section: Introductionmentioning
confidence: 99%